Electrolytically Generated Manganese(III) Sulphate for the Oxidation of 6-Deoxyhexoses in Aqueous Sulphuric Acid Medium: A Kinetic Study - Rangappa, K.S.; Anitha, N.; Ayesha Nikath, M.; Thimme Gowda, A. (Asian Journal of Chemistry, 2010)
Manganese(III) sulphate was prepared by the electrolytic oxidation of manganese(II) sulphate in aqueous sulphuric acid. The electrolytically generated Mn(III) species was characterised by spectroscopic and redox potential studies. Conditions for the study of kinetics of oxidation of 6-deoxy hexoses namely L-rhamnose and L-fucose by Mn(III) in aqueous sulphuric acid were investigated at λmax = 500 nm spectrophotometrically. The rate shows ftrst order dependence on [Mn(III)]0 and [S]0 but there is no dependence of rate on [H+]. The effects of added anions like chloride, sulphate, fluoride, persulphate and reaction product Mn(II) were investigated. Kinetic and thermodynamic parameters were computed from Arrhenius and Eyring plots. A mechanism involving the formation of enediol from 6-deoxyhexose which react with Mn(III) in the rate limiting step is suggested.